Advanced Virtual Assistants - A Window to the Virtual Future (IntechOpen, 2024)
Advanced Virtual Assistants (AVAs) are computer programs that use artificial intelligence (AI) to perform various tasks for human users. These AI-powered assistants can help with multiple activities, including scheduling appointments, answering questions, managing email and social media, and even performing complex calculations. They can be accessed through various platforms, including smartphones, smart speakers, and other digital devices. AVAs utilize natural language processing (NLP) and machine learning algorithms to understand human language and improve their responses over time. As these technologies advance, virtual assistants are becoming increasingly sophisticated and capable of handling more complex tasks. As a result, they are transforming how we interact with technology and providing users with more efficient and personalized experiences. This book is a helpful reference for scientists and industrial experts interested in AVAs' current and future capabilities.